Expectation-driven term structure of equity and bond yields - Ming Zeng; Guihai Zhao (Bank of Canada, 2022)
Recent findings on the term structure of equity and bond yields pose serious challenges to existing models of equilibrium asset pricing. This paper presents a new equilibrium model of subjective expectations to explain the joint historical dynamics of equity and bond yields (and their yield spreads). The movements of equity and bond yields are driven mainly by subjective expectations of dividend and gross domestic product (GDP) growth. Yields on short-term dividend claims are more volatile because the expected short-term dividend growth meanreverts to its less volatile long-run counterpart. The procyclical slope of equity yields is due to the countercyclical slope of dividend growth expectations. The correlation between equity returns/yields and nominal bond returns/yields switched from positive to negative after the late 1990s, owing mainly to a stronger correlation between expectations of real GDP growth and real dividend growth and only partially to procyclical inflation. Dividend strip returns are predictable, and the predictive power decreases with maturity as a result of predictable forecast errors and revisions. The model is also consistent with the data in generating persistent and volatile price-dividend ratios and excess return volatility.
Keywords: G00; G12; E43; 330; Asset pricing; Financial markets; Interest rates